ANALYSIS OF RETURN AND RISK ACCORDING IN THE INVESTMENT PORTFOLIO STYLE: AN ANALYTICAL STUDY OF A SAMPLE OF IRAQI BANKS IN THE IRAQI STOCK EXCHANGE FOR THE PERIOD (2016-2020) - Assistant Professor Dr. Iftikhar Jabbar Abed (Scholar Express Journals, 2024)
The aim of the current research is to measure the effect of the investment portfolio method in maximizing returns and reducing risks for banks by attracting investments in the Iraqi stock market, and the aim of the research is to how to manage the investment portfolio of private Iraqi commercial banks (Bank of Baghdad, Investment Bank, Commercial Bank, Sumer Bank) in the Iraqi Stock Exchange in a way that achieves the highest return and the least risk. Statistical methods were used such as the variance rate, standard deviation, and beta coefficient in measuring the return and risk of stocks to analyze the data. The research reached a set of conclusions, the most important of which was the fluctuation of the achieved return for stocks and the achieved return. market during the study period, as well as the change in risk for bank stocks during the study period.
Keywords: return; risk; investment portfolio; Iraq Stock Exchange